Implementasi Kepastian Hukum dan Dampaknya terhadap Keberlanjutan Pariwisata di Desa Wisata Sada Lombok - Titin Apriani; Ni Luh Ariningsih Sari (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The development of tourism villages as part of a sustainable tourism strategy requires governance supported by strong legal certainty. Sada Lombok Tourism Village is a cultural-based destination that has developed through the involvement of local communities and traditional institutions in its management. However, this governance dynamic is not free from legal challenges that may affect tourism sustainability. This study aims to analyze the implementation of legal certainty in the management of Sada Lombok Tourism Village and its impact on tourism sustainability from economic, socio-cultural, and environmental perspectives. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, field observations, and document analysis of village regulations and tourism-related policies. The findings indicate that although village regulations and customary norms governing tourism management are in place, the implementation of legal certainty remains partial and not yet fully integrated. This condition affects economic sustainability, poses potential risks to the protection of cultural values, and limits effective environmental management. The study emphasizes that strengthening legal certainty through regulatory harmonization, formal recognition of traditional institutions, and increased community participation is a crucial prerequisite for achieving sustainable tourism in Sada Lombok Tourism Village. The findings are expected to contribute both theoretically and practically to the development of community-based tourism villages that are equitable and sustainable.